MANAGING THE PRODUCTION PROCESSES - OPTIMIZATION OF THE TECHNOLOGICAL PROCESS OF BANANA RIPENING BY APPLYING THE SIMPLE ADDITIVE WEIGHTING METHOD - Stojanović, Ivan; Jovanović, Violeta; Manić, Aleksandar (Economics of Agriculture, 2023)
The realization of company goals is greatly influenced by the manager’s decisions in the activities of managing production processes. To make decisions, managers use different decision-making methods, taking into account different criteria on the basis of which they choose the best alternative. The paper presents the optimization of the technological process of banana ripening using the simple additive weighting (SAW) method. The research monitored temperature correction, ripening gas dosage concentration, duration of treatment, commodity loss, including correction of accompanying factors of green banana fruit ripening. By applying the SAW method on 400 performed ripenings in the period from 2017 to 2020, the best results were achieved at a temperature of 18.5 °C, with an ethylene concentration of 840 ppm, process time of 112 h and achieved kalo of 233 kg. The total cost of ripening based on the examined parameters is 250.12 € which can save 81.42 € and meet the finishing standards.